The Level of Total Quality Standers Implementation among Distance Learning from Principals Perspective of Public School in Al-Zarqa First Directorate - Almaaitah, Husni Tahseen Mohammad (Journal of Educational and Psychological Sciences, 2021)
This Study aimed to identify the level of total quality standers implementation among distance learning from principals perspective of public school in al-zarqa first directorate, and to determine the effect of variables (sex, and years of experience), the researcher used the Descriptive approaches, study sample consisted of (109) Female and male principal in Al- first Zarqa directorate, to collect data Questioner used, the result shown that the level of total quality standers implementation among distance learning from Principals perspective of public school in al-zarqa first directorate was moderated , The finding also showed there is no statistically significant differences at (α≤0.05) refers to principal sex (male and female) in addition there were statistically significant differences between the principals years of experience in favor of (10 years and more).